Inclusive service delivery for persons with disabilities in Mongolia. (Metro Manila, Philippines Asian Development Bank, 2018)
Estimates of disability prevalence in Mongolia tend to be underreported, especially among older people, girls, and women, thus leaving a substantial number of persons with disabilities (PWDs) without the necessary services and protection. Early identification of disability is inadequate and current disability assessments follow an outdated, narrow medical approach. Many people perceive PWDs to be incapable of living independently and a burden to society.In 2017, ADB approved a concessional loan of 25 dollar million and a grant from the Japan Fund for Poverty Reduction of 2 dollar million to help finance a project that will support the Government of Mongolia to address major economic, social, and rights issues of PWDs in Mongolia. The project, Ensuring Inclusiveness and Service Delivery for Persons with Disabilities, aims to ensure access to services and employment for PWDs to increase their autonomy and contribution to the economy and society in general.
Keywords: Social rights -- Mongolia; Electronic books